Analysis of the Role of the Transportation and Telecommunication Sector on the Gross Regional Domestic Product (GRDP) of North Sumatra - Aidil Fitriadi Fahruky (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2022)
The purpose of this study was to determine the role of the transportation and telecommunications sector on the GRDP of the transportation and telecommunications sector of North Sumatra. In collecting data the author uses secondary data collection techniques. Granger Causality test approach to see the causal relationship between the length of the road and telephone users of Telkom to the GRDP of North Sumatra. and the OLS (Ordinary Least Square) method or the Ordinary least squares method with the help of the E-Views 5.1 program.After conducting theoretical research and test results on the diagnosed hypotheses, in this case, it can be concluded that the length of the road and Telkom telephone users have a role in the formation of GRDP in the transportation and telecommunications sector of North Sumatra. Based on the Granger causality test analysis, the relationship between road length and the GRDP of the transportation and telecommunications sectors shows a one-way relationship, as well as between Telkom telephone users and the GRDP of the transportation and telecommunications sectors, which shows a one-way relationship. And the OLS analysis obtained Estimation Results Y = -18.91450 + 1.584108X1 + 0.894272 X2, meaning that the transportation and telecommunications sector has a significant role in the formation of the GRDP of the transportation and telecommunications sector in North Sumatra.